형광과 레이저 스펙클 대조도 이미징을 결합한 실시간 의료영상 시스템 개발 - 심민재; 김이근; 고택용; 최진혁; 안예찬; Shim, Min Jae; Kim, Yikeun; Ko, Taek Yong; Choi, Jin Hyuk; Ahn, Yeh-Chan (Journal of biomedical engineering research, 2021)
It is important to differentiate between the target tissue (or organ) and the rest of the tissue before incision during surgery. And when it is necessary to preserve the differentiated tissues, the blood vessels connected to the tissue must be preserved together. Various non-invasive medical imaging methods have been developed for this purpose. We aimed to develop a medical imaging system that can simultaneously apply fluorescence imaging using indocyanine green (ICG) and laser speckle contrast imaging (LSCI) using laser speckle patterns. We designed to collect images directed to the two cameras on a co-axial optical path and to compensate equal optical path length for two optical designs. The light source used for fluorescence and LSCI the same 785 nm wavelength. This system outputs real-time images and is designed to intuitively distinguish target tissues or blood vessels. This system outputs LSCI images up to 37 fps through parallel processing. Fluorescence for ICG and blood flow in animal models were observed throughout the experiment.